The Effect of Financial Restructuring, Firm Size and Sales Growth on Firm Performance (Balance Scorecard): The Case of State-Owned Enterprises in Indonesia - Ulandari, Melita; Ladewi, Yuhanis; Yamaly, Fadhil (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This study aims to determine and analyze the Effects of Financial Restructuring, Company Size, and Sales Growth on Company Performance (as measured by the Balanced Scorecard) in BUMN Companies throughout Indonesia. The population in this study consisted of 21 BUMN Companies that underwent restructuring. The Sampling Technique used in this study was Purposive Sampling. In this study, the samples consisted of 9 companies that published complete financial reports and performance reports and carried out restructuring from 2018 to 2023. The analysis technique employed was multiple linear regression. The results of this study indicate that financial restructuring, company size, and sales growth together have a significant effect on company performance (balanced scorecard), partially financial restructuring does not affect company performance (balanced scorecard), company size affects company performance (balanced scorecard), and sales growth affects company performance (balanced scorecard). These findings have practical implications for financial restructuring and company performance in the BUMN sector.